2021
DOI: 10.1177/0272989x211011101
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Health Literacy in Patient Decision Aids: An Update from the International Patient Decision Aid Standards

Abstract: Background There is increasing recognition of the importance of addressing health literacy in patient decision aid (PtDA) development. Purpose An updated review as part of IPDAS 2.0 examined the extent to which PtDAs are designed to meet the needs of people with low health literacy/socially-disadvantaged populations. Data Sources Reference lists of Cochrane reviews of randomized controlled trials (RCTs) of PtDAs (2014, 2017, and upcoming 2021 versions). Study Selection RCTs that assessed the impact of PtDAs on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 46 publications
1
39
0
Order By: Relevance
“…A recent review of DAs for people with lower health literacy [ 57 , 58 ] showed that DAs that use health literacy design strategies lead to improved knowledge, decisional conflict, and decision-making outcomes. Furthermore, DAs that used explicit strategies to reduce cognitive burden showed greater improvements in knowledge for people with low health literacy and from disadvantaged backgrounds [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of DAs for people with lower health literacy [ 57 , 58 ] showed that DAs that use health literacy design strategies lead to improved knowledge, decisional conflict, and decision-making outcomes. Furthermore, DAs that used explicit strategies to reduce cognitive burden showed greater improvements in knowledge for people with low health literacy and from disadvantaged backgrounds [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…33 As recommended by IPDAS, the mammography DA was written at a sixth-grade reading level using low literacy principles and uses large font, bullet points, short sentences, and includes illustrations; yet, many PCPs were still concerned about its literacy level. 34 Therefore, investigators have recently developed and pilot tested an even lower literacy mammography DA for women 75 years. 35 The modified DA (also available at ePrognosis) is shorter than the original DA and does not use pictographs since older women with low health literacy who evaluated the original DA found the pictographs difficult to understand.…”
Section: Varying Views On Acceptabilitymentioning
confidence: 99%
“…7 However, processing and using the information in decision-support tools is not easy, especially for patients with lower health literacy (HL) and/or numeracy. 8 Therefore, it is important to design decision-relevant information that suits the needs of patients and at the same time is clear for patients with diverse levels of HL/numeracy. 8,9 The WHO definition of HL is: 'the cognitive and social skills which determine the motivation and ability of individuals to gain access to, understand, and use information in ways which promote and maintain good health' 10 In Europe, 47% of the population has too few skills to understand and use health information correctly to make health-related decisions.…”
Section: Introductionmentioning
confidence: 99%